Effect of Physical Activity on Self‐Reported Disability in Older Adults: Results from the LIFE Study. Issue 5 (7th February 2017) - Manini, Todd M.; Beavers, Daniel P.; Pahor, Marco; Guralnik, Jack M.; Spring, Bonnie; Church, Timothy S.; King, Abby C.; Folta, Sara C.; Glynn, Nancy W.; Marsh, Anthony P.; Gill, Thomas M.
Abstract : Background/Objectives: To test the hypothesis that a long‐term structured, moderate intensity physical activity (PA) program is more effective than a health education (HE) program in reducing the risk of s elf‐reported dependency and disability in basic activities of daily living (BADLs), disability in instrumental ADLs (IADL), and mobility disability. Design: The Lifestyle Interventions and Independence for Elders (LIFE) study was a multicenter, single‐blinded randomized trial. Setting: University‐based research clinic. Participants: Thousand six hundred and thirty five sedentary men and women aged 70–89 years, who had functional limitations, defined as a score ≤9 on the Short Physical Performance Battery. Intervention: Participants were randomized to a structured, moderate intensity PA program (n = 818) that included aerobic, resistance, and flexibility exercises or to a HE program (n = 817). Measurements: All outcomes were derived by self‐report using periodic interviews that asked about the degree of difficulty and receipt of help during the past month. Dependency was defined as "receiving assistance" or "unable" to do ≥1 activities. Disability was defined as having "a lot of difficulty" or "unable" doing ≥1 activities. Severe disability was defined as reporting difficulty or being unable to perform ≥3 activities. Results: Over an average follow‐up of 2.6 years, the cumulative incidence of BADL dependency was 15.2% among PA and 15.1% among HE participants (HR = 1.0, 95% CI = 0.78–0.1.3). Intervention groups had similar rates of incident BADL disability, IADL disability and reported mobility disability. Reporting severe mobility disability (HR = 0.78, 95% CI = 0.64–0.96) and ratings of difficulty on mobility tasks were reduced in the PA group. Conclusion: A structured physical activity intervention reduces reported severe mobility disability and difficulty on mobility tasks, but not BADL and IADL disability in older adults with functional limitations.